Perbandingan Morfometrik Kambing Kacang yang Dipelihara Secara Semi Intensif dan Intensif di Kabupaten Kampar, Provinsi Riau - Azmidaryanti, R.; Misrianti, R.; Siregar, S. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
The aim of this research was to compare morphometric of kacang goat in different system. A number of 247 heads kacang goat, consist of 86 male heads ( 49 heads from semi-intensive system, 37 heads from intensive system), and 261 female heads (109 heads from semi-intensive and 52 heads from intensive system).. The parameters used in this research were length of the animal face, the length of the ear, the chest circle, the widhest of the cheast, the depth of the cheast, the length of the animal body, the tall of the shoulder, the height of the hill, the widest of the back, the height of the front legs, the height of the back legs, the length of the tail, and the weight of the body. The differences between semi-intensive and intensive system of  kacang goat will be analyzed by t-test. The results of the test indicated that the length of the ears, the widest of the cheast, the height of the front legs, and the length of the back legs of the male kacang goat rearing semi intensively and intensively were not significantly diffrent, while the average of the length of the face, the cheast circle, the length of the body, the height of the shoulder, the height of the hill,the widest of the back hill, the length of the tail, and the weight of the body of the male kacang goat were significantly different, semi-intensive system was small than intensive system. The average of the length of the face, the length of the ear, the circle of the cheast, the widest of the cheast, the deep of the cheast, the length of the body, the height of the shoulder, and the height of the back body, the widest of the back, the length of the front legs, the length of the back legs, the length of the tail, and the weight of the body animal from semi intensive system in Kampar Regency were significantly different. The morphometric of kacang goat from semi-intensive system was small than intensive system.